Phenolic acid content and sensory properties of two Spanish monovarietal virgin olive oils. Issue 6 (11th March 2013) - Rivas, Ana; Sanchez‐Ortiz, Araceli; Jimenez, Brigida; García‐Moyano, Jesus; Lorenzo, Maria Luisa
Abstract In recent years, phenolic acids have received considerable attention as they are essential to olive oil quality and nutritional properties. This study aims to validate a rapid and sensitive method based on ultra‐performance liquid chromatography/time‐of‐flight mass spectrometry (UPLC–TOF‐MS) for analyzing the phenolic acid content of olive oil and assessing its impact on virgin olive oil (VOO) sensory attributes. Once this method was validated, we used it to evaluate the phenolic acid composition of several Spanish monovarietal virgin olive oils in relation to nine different olive ripening stages. The results obtained confirm that the methodology developed in this study is valid for extracting and analyzing phenolic acids from VOO. The phenolic acid content of the virgin olive oils sampled was proven to be influenced by the type of cultivar and olive harvest date. Therefore, phenolic acids might be used as potential markers for olive oil cultivar or ripening stage. Finally, the data obtained indicate that the sensory properties of VOO may be differently affected by its phenolic acid content depending on the type of cultivar. Practical applications: The method validated in the present study – based on UPLC‐TOF‐MS – allows experts to assess the phenolic acid content of different VOO cultivars (varieties). This application will probably be very useful to the olive oil industry. The reason is that our study revealed that phenolic acids have an impact on the sensory quality of VOO, which is essential to consumer preferences and choice. In addition, there are phenolic acids that are only found in a particular variety of olive oil obtained from fruits at a specific ripening stage. Consequently, phenolic acids could be used as potential markers for olive oil variety and harvest time.